Redox classification and calibration of redox thresholds in sedimentary systems - Algeo, Thomas J.; Li, Chao (Geochimica et cosmochimica acta, 2020)
•Review of environmental redox classifications.•Calibration of commonly used elemental proxies to redox facies.•Analysis of proxies from modern Black Sea, Saanich Inlet, and California Margin.•Use of compound covariation of redox proxies to identify key redox thresholds.•No universal proxy values: calibration necessary for each depositional system under study. Existing redox classifications and the calibrations of elemental proxies to modern environmental redox scales are in need of re-evaluation. Here, we review environmental redox classifications, commonly used elemental redox proxies, and their intercalibration, and we propose a novel approach to improve the calibration of such proxies, using datasets from the modern Black Sea, Saanich Inlet, and California Margin as examples. Our approach is based on recognition of compound covariation patterns among pairs of elemental redox proxies within a redox framework based on three key thresholds: (1) the Re4+/Re3− couple near the suboxidized/subreduced boundary of the suboxic zone, (2) the U6+/U4+ couple in the middle of the subreduced zone, and (3) the SO42−/H2S couple at the suboxic/euxinic boundary. Within this framework, it is possible to determine the relative timing of onset and the degree of enrichment of other elemental redox proxies. Our analysis demonstrates that, even though some elements exhibit limited enrichment within the suboxic zone, the bulk of authigenic enrichment of the redox-sensitive elements considered in this study occurs within the euxinic zone. One important finding of our study is that the threshold value associated with a given elemental proxy can vary considerably between depositional systems. For this reason, it is inadvisable to transfer published threshold values (i.e., from earlier paleoredox studies) to completely different formations, and redox proxies must be internally calibrated for each individual paleodepositional system under investigation.